Identification of active sites in CO oxidation and water-gas shift over supported Pt catalysts - Ding, Kunlun; Gulec, Ahmet; Johnson, Alexis M; Schweitzer, Neil M; Stucky, Galen D; Marks, Laurence D; Stair, Peter C (Science (American Association for the Advancement of Science), 2015)
Identification and characterization of catalytic active sites are the prerequisites for an atomic-level understanding of the catalytic mechanism and rational design of high-performance heterogeneous catalysts. Indirect evidence in recent reports suggests that platinum (Pt) single atoms are exceptionally active catalytic sites. We demonstrate that infrared spectroscopy can be a fast and convenient characterization method with which to directly distinguish and quantify Pt single atoms from nanoparticles. In addition, we directly observe that only Pt nanoparticles show activity for carbon monoxide (CO) oxidation and water-gas shift at low temperatures, whereas Pt single atoms behave as spectators. The lack of catalytic activity of Pt single atoms can be partly attributed to the strong binding of CO molecules.